2016
DOI: 10.1103/physrevd.94.054039
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of theP-wave diproton resonance in single-pion production inppcollisions

Abstract: It is demonstrated that many important features of single-pion production in pp collisions at intermediate energies (T p ≃ 400-800 MeV) can naturally be explained by supposing excitation of intermediate diproton resonances in pp channels 1 D 2 , 3 F 3 and 3 P 2 , in addition to conventional mechanisms involving an intermediate ∆-isobar. We predict for the first time the crucial role of the 3 P 2 diproton resonance, found in recent experiments on the single-pion production reaction pp → pp( 1 S 0 )π 0 , in repr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 97 publications
(161 reference statements)
6
14
0
Order By: Relevance
“…The main argument however is that in the ground of the dibaryon concept there is an experimentally verified assumption about the dominating role of dibaryon resonances in NN interaction in each partial-wave channel. Besides, the present authors have shown in a series of papers [42][43][44] that the observed dibaryon characteristics are in good agreement with the experimental cross sections for one-and two-pion production in NN collisions at intermediate energies T N ∼ 1 GeV.…”
Section: Dibarion Model For Nuclear Force a Qualitative Considerationsupporting
confidence: 86%
See 2 more Smart Citations
“…The main argument however is that in the ground of the dibaryon concept there is an experimentally verified assumption about the dominating role of dibaryon resonances in NN interaction in each partial-wave channel. Besides, the present authors have shown in a series of papers [42][43][44] that the observed dibaryon characteristics are in good agreement with the experimental cross sections for one-and two-pion production in NN collisions at intermediate energies T N ∼ 1 GeV.…”
Section: Dibarion Model For Nuclear Force a Qualitative Considerationsupporting
confidence: 86%
“…It is important to note here that a similar conclusion about the dominance of the dibaryon mechanism in inelastic NN interaction in the 3 P 2 channel was made by us when analyzing the single-pion production reaction pp → dπ + at energies from the threshold to about 800 MeV [44].…”
Section: Channel 3 Psupporting
confidence: 79%
See 1 more Smart Citation
“…Only by inclusion of the formation and the decay of dibaryon resonances -in particular the D 12 resonance with I(J P ) = 1(2 + ) in the 1 D 2 N N partial wave -in the intermediate reaction process a proper description of the experimental data can be obtained. By additional inclusion of corresponding resonances in 3 F 3 and 3 P 2 partial waves even polarization observables can be quantitatively described for the first time [207].…”
Section: A Possible Remnant From This Period -A Broad Resonance Strucmentioning
confidence: 99%
“…There is suggestive evidence for the existence of still further states like a P -wave I(J P ) = 1(3 − ) state, for which, however, the experimental situation is not yet as clear [16]. It is also worth emphasising that the three resonances 1(2 + ), 1(2 − ) and 1(3 − ) have been shown to give a sizeable contribution to the pp → dπ + cross sections and polarisation observables [31] (the resonance 1(0 − ) is not allowed in this reaction by the parity and momentum conservation).…”
Section: Introductionmentioning
confidence: 98%